Optimization model for fire station location based on GIS and python: A case study in north cyprus - Kazemi, Mahdi; Kunt, Mehmet Metin; Aghayan, Iman; Jalali Larijani, Reza (My University, 2013)
In this paper, the location selection process related to fire stations in Famagusta city is enhanced by applying Quantum Geographic Information Systems (QGIS) and Python programming language. This procedure leads to obtaining the optimum emergency service location based on the minimization of response time. This study aims to commence service coverage modeling in a consistent demand region, with road availability considerations. In addition, this study focuses on the capability of GIS to create service areas by means of the travel time regions in a facility location model. Another purpose of this research is to maximize the overall service area of the determined number of facilities and to state the capability of GIS for establishing the suitable service areas of fire stations in Famagusta city so as to achievie a maximal overall service area from a specific fire station facility to other locations. The best location for only one fire station is determined which is placed around the signalized intersection joining Mustafa Kemal Boulevard and Topçular Boulevard in Famagusta (node 230). © (2013) Trans Tech Publications, Switzerland.
2nd International Conference on Materials Engineering and Automatic Control, ICMEAC 2013 --
Keywords: Famagusta city; Fire station location; Geographic information system; Optimization model; Python